Pelatihan Analisis Regresi Linear Berganda dalam Menyelesaikan Tugas Akhir Mahasiswa Stia Setih Setio Muara Bungo - Tarjo Tarjo; Yasmir Tarjo (Jurnal Abdimas Adpi Sosial dan Humaniora, 2022)
Research is a scientific work for final year students, therefore students are required to be able to analyze research data. The preparation of scientific papers for final year students is still constrained in terms of data processing using statistics, thus submitting it to other parties. Therefore, assistance and training are needed using an application, one of which is SPSS to analyze multiple linear regression. The obstacle faced by students so far is analyzing data with statistics. This method of community service by training and mentoring students of the business administration study program at the Setih Setio Muara Bungo School of Administration in completing the final project, targeted 30 participants, but 54 people registered. The results of this training show that it is useful to complete the task, the success rate of this training is 81.4%. In the future, there should be more practice in class so that students don't forget when doing research.